Effects of a very high saturated fat diet on LDL particles in adults with atherogenic dyslipidemia: A randomized controlled trial. - Sally Chiu; Paul T Williams; Ronald M Krauss (PLoS ONE)
Background Previous studies have shown that increases in LDL-cholesterol resulting from substitution of dietary saturated fat for carbohydrate or unsaturated fat are due primarily to increases in large cholesterol-enriched LDL, with minimal changes in small, dense LDL particles and apolipoprotein B. However, individuals can differ by their LDL particle distribution, and it is possible that this may influence LDL subclass response. Objective The objective of this study was to test whether the reported effects of saturated fat apply to individuals with atherogenic dyslipidemia as characterized by a preponderance of small LDL particles (LDL phenotype B). Methods Fifty-three phenotype B men and postmenopausal women consumed a baseline diet (55%E carbohydrate, 15%E protein, 30%E fat, 8%E saturated fat) for 3 weeks, after which they were randomized to either a moderate carbohydrate, very high saturated fat diet (HSF; 39%E carbohydrate, 25%E protein, 36%E fat, 18%E saturated fat) or low saturated fat diet (LSF; 37%E carbohydrate, 25%E protein, 37%E fat, 9%E saturated fat) for 3 weeks. Results Compared to the LSF diet, consumption of the HSF diet resulted in significantly greater increases from baseline (% change; 95% CI) in plasma concentrations of apolipoprotein B (HSF vs. LSF: 9.5; 3.6 to 15.7 vs. -6.8; -11.7 to -1.76; p = 0.0003) and medium (8.8; -1.3 to 20.0 vs. -7.3; -15.7 to 2.0; p = 0.03), small (6.1; -10.3 to 25.6 vs. -20.8; -32.8 to -6.7; p = 0.02), and total LDL (3.6; -3.2 to 11.0 vs. -7.9; -13.9 to -1.5; p = 0.03) particles, with no differences in change of large and very small LDL concentrations. As expected, total-cholesterol (11.0; 6.5 to 15.7 vs. -5.7; -9.4 to -1.8; p<0.0001) and LDL-cholesterol (16.7; 7.9 to 26.2 vs. -8.7; -15.4 to -1.4; p = 0.0001) also increased with increased saturated fat intake. Conclusions Because medium and small LDL particles are more highly associated with cardiovascular disease than are larger LDL, the present results suggest that very high saturated fat intake may increase cardiovascular disease risk in phenotype B individuals. This trial was registered at clinicaltrials.gov (NCT00895141). Trial registration Clinicaltrials.gov NCT00895141.